Análise do discurso ambiental em redes sociais da indústria automotiva no Brasil - Camargo, Arthur Ferraz de (Universidade Federal de São Carlos, 2024)
Faced with the urgency of climate and environmental crises, environmentalism must not only identify culprits but also propose viable solutions. This dilemma is particularly evident in the contradiction between the pursuit of true sustainability and a production and consumption model fundamentally driven by planned obsolescence. As a pioneer in mass production, the automotive industry played a central role in shaping the Consumer Society, reinforcing the corporate need to expand consumption incentives. Today, within a consumption-based system, advertising has become the most powerful form of discourse, facilitated by seamless communication between individuals, corporations, and political entities. In this context, our objective was to describe and analyze the environmental discourse of the automotive industry in Brazil, examining its structure and intent to uncover convergences and divergences between corporate practices, advertising narratives, and global climate reality. To achieve this, we conducted a narrative literature review on the relationship between consumer society and automobiles, with environmentalism as the guiding theme that could exposes contradictions. We then carried out a documentary research study, analyzing 1,687 Instagram posts published in 2022 by Brazil’s top-selling car manufacturers. The analysis considered 27 attributes, counting discursive ones and metadata. From these data, we examined how each brand approach environmental themes and, through data aggregation and clustering, inferred the industry's overall stance. We also analyzed discursive attributes to identify biases, omissions, and the extent to which the discourse aligns with—or contradicts—reality. Our findings indicate that, in practice, the automotive industry does the bare minimum to comply with regulations. At the same time, in the vast majority of cases, its environmental discourse is shallow and generic, avoiding any substantive discussion of sustainability and environmental issues. Ultimately, it becomes evident that the sector is not sustainable, as a coherent discourse is just as essential as good actions. If the industry is ever to become truly sustainable, it will have to confront deep-rooted structural challenges inherent to consumer society itself—an outcome that, at present, seems highly unlikely.
Analysis of environmental discourse on social media in the brazilian automotive industry
Keywords: Setor automotivo; Indústria automobilística; Publicidade ambiental; Consumerism; Greenwashing; Greenhushing; Automotive sector; Automobile industry; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::RELACOES PUBLICAS E PROPAGANDA